2016
DOI: 10.1080/01441647.2016.1252446
|View full text |Cite
|
Sign up to set email alerts
|

Exploring active transportation investments and associated benefits for municipal budgets: a scoping review

Abstract: Municipalities play an important role in the planning and development of communities that support active transportation (AT), which refers to human-powered modes of travel, such as walking and cycling. Municipal-level stakeholders involved in landuse and transportation infrastructure planning consider multiple social, environmental and economic considerations to inform decision-making and investments in AT. Evidence around the fiscal benefits of AT investment for local governments has not been systematically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 45 publications
1
3
0
3
Order By: Relevance
“…This article reviews the main findings of the study “Riding towards the green economy: cycling and green jobs” [ 11 ], developed in the context of the Transport, Health and Environment Pan European Programme (THE PEP). As with previously published studies that present evidence of employment-generation from active transportation investments [ 12 ], the reviewed paper demonstrates that, in addition to its important environment and health benefits, cycling also has significant job creation potential.…”
Section: Introductionsupporting
confidence: 65%
“…This article reviews the main findings of the study “Riding towards the green economy: cycling and green jobs” [ 11 ], developed in the context of the Transport, Health and Environment Pan European Programme (THE PEP). As with previously published studies that present evidence of employment-generation from active transportation investments [ 12 ], the reviewed paper demonstrates that, in addition to its important environment and health benefits, cycling also has significant job creation potential.…”
Section: Introductionsupporting
confidence: 65%
“…We focused on studies in the US and Canada in large part because opposition to new active travel facilities has often been fierce in those two countries (Bubbers, 2019;Chapple et al, 2018;Sadik-Khan, 2016), making this research particularly relevant and useful for planners and policymakers there. In addition, a preliminary review of our search records indicated that the vast majority of relevant English-language studies were done in the US and Canada, which is unsurprising given the relative surge in active travel projects (and accompanying opposition) there compared to European countries with more established active travel facilities (Kornas, Bornbaum, Bushey, & Rosella, 2017;Pucher, Buehler, & Seinen, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Во-вторых, транспортная устойчивость достигается за счет повышения доли «зеленого транспорта», использование которого дает меньший уровень загрязнения: новых видов углеводородного топлива, электротранспорта [Ronanki, Kelkar, Williamson, 2019] и велосипедов [Larsen, El-Geneidy, Yasmin, 2010;Kornas et al, 2017]. В 2019 г. в Санкт-Петербурге на нескольких маршрутах в северной и центральной частях города начала движение экспериментальная партия электробусов -автобусов и троллейбусов на электротяге.…”
Section: взаимосвязь транспортной политики и элементов городаunclassified
“…Таким образом, положительное изменение экологической обстановки неизбежно оказывает влияние не только на здоровье жителей, но и на экономические показатели развития города [Kornas et al, 2017]. Поэтому развитие транспортной системы в рамках концепции устойчивого развития может не только улучшить экологическую ситуацию, но и дать ощутимые экономические выгоды для городского развития.…”
Section: взаимосвязь транспортной политики и элементов городаunclassified